ChemInform Abstract: Solid‐State Crystal‐to‐Crystal Phase Transitions and Reversible Structure—Temperature Behavior of Phosphovanadomolybdic Acid, H5PV2Mo10O40. Issue 13 (March 2015) - Barats‐Damatov, Delina; Shimon, Linda J. W.; Feldman, Yishay; Bendikov, Tatyana; Neumann, Ronny
Abstract The crystal packing and secondary structure of H5PV2Mo12O40 (prepared according to the literature) is analyzed by powder XRD and reveals 4 unique structures (36, 14, 8 units of crystal H2O, the latter in two modifications) and 3 reversible solid phase transitions between 25 and 55 °C depending on the loss of solvated H2O and concomitant contraction of the cell volume and increase of packing density.